Perspective of the frontolateral craniotomies Perspectivas das craniotomias frontolaterais - Eberval Gadelha Figueiredo; Arthur Maynart Pereira Oliveira; José Píndaro P Plese; Manoel Jacobsen Teixeira (Arquivos de Neuro-Psiquiatria)
The pterional craniotomy is one of the most frequently surgical approaches used in neurosurgery and currently it has become a mainsteam. It allows excellent microsurgical exposure of anterior and posterior regions of the arterial circle of Willis, supra and paraselar regions, the superior orbital fissure of sphenoid bone, cavernous sinus, orbit, temporal lobe, midbrain and the frontal lobe. Like others techniques, the pterional craniotomy presented disadvantages related to dissection of the temporal muscle. From the first fronto lateral craniotomy described by Dandy to expose the optic chiasm and the pituitary we pass through the Yasargil's classical description of craniotomy centered in fronto-temporal sylvian fissure until reaching the recent"minipterional craniotomy", modifications of the pterional craniotomy were proposed to reduce the extra cranial tissue trauma and reduce the area of craniotomy without affecting the exposure of surgical targets, thus improving their aesthetic and functional results. An historical analysis of the frontolateral approaches has demonstrated that they have evolved from larger craniotomies to smaller ones, however only the minipterional craniotomy is able to offer similar surgical exposure. A craniotomia pterional é um dos acessos cirúrgicos mais freqüentemente utilizados. Esta técnica permite excelente exposição microcirúrgica das regiões anterior e posterior do polígono de Willis, regiões supra-selar, fissura orbital superior do osso esfenóide, seio cavernoso, órbita, lobo temporal, mesencéfalo e lobo frontal. Como outras técnicas, a craniotomia pterional tem desvantagens relacionadas à manipulação do músculo temporal. Desde a primeira craniotomia fronto lateral descrita por Dandy para expor o quiasma óptico e a hipófise, passando pela descrição clássica de Yasrgil para craniotomia centrada na fissura silviana, até chegar em craniotomias recentes como a"minipterional", modificações da craniotomia pterional foram propostas para reduzir o trauma do tecido extra craniano e reduzir a área da craniotomia sem afetar a exposição dos alvos cirúrgicos e melhorar seus resultados estéticos e funcionais. Uma análise histórica das abordagens frontolaterais demonstrou que elas evoluíram a partir de craniotomias maiores para menores, contudo somente a craniotomia minipterional oferece exposição cirúrgica similar à craniotomia pterional clássica.